Virus-derived siRNAs and piRNAs in immunity and pathogenesis. - Ding, S.W.; Lu, R. (Current opinion in virology, 2011)
Cellular organisms have evolved related pathways for the biogenesis and function of small interfering RNAs (siRNAs), microRNAs and PIWI-interacting RNAs (piRNAs). These distinct classes of small RNAs guide specific gene silencing at both transcriptional and posttranscriptional levels by serving as specificity determinants. Small RNAs of virus and host origins have been found to modulate virushost interactions by RNA interference (RNAi), leading to antiviral immunity or viral pathogenesis. Deep sequencing-based profiling of virus-derived small RNAs as products of host immune recognition not only allowed us to gain insight into the expansion and functional specialization of host factors involved in the antiviral immunity but also made it possible to identify new viruses in a culture-independent manner. Here we review recent developments on the characterization and function of virus-derived siRNAs and piRNAs in eukaryotic hosts.